2021
DOI: 10.3390/universe7020029
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of ULF/ELF/VLF Waves in the Ionosphere by Modulated Heating

Abstract: One of the most important effects of ionospheric modification by high power, high frequency (HF) waves is the generation of ultra low frequency/extremely low frequency/very low frequency (ULF/ELF/VLF) waves by modulated heating. This paper reviews the scientific achievements of the past five decades regarding the main mechanisms of excitation of ULF/ELF/VLF waves and discusses their characteristics, such as their electrojet dependency, the location of the source region, continuous and discontinuous waves, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In addition, ambient power‐line harmonics (Fedorov et al., 2021 ; Park & Helliwell, 1978 ), intentional VLF transmissions from terrestrial power lines and high‐power VLF transmitters can leak into space where they may interact with energetic electrons in the Earth's magnetosphere (Hua et al., 2020 ; Ma et al., 2017 ; Ross et al., 2019 ). Several man‐made facilities have been developed to study this wave‐particle‐interaction process including VLF transmitters (Helliwell, 1977 , 1988 ), high‐power HF facilities for modulations of natural ionosphere currents in the ionosphere (Guo et al., 2021 ), large satellite antennas driven by high power signal generators, electron beams that are modulated at VLF rates, and high‐speed neutral injections that rapidly photoionize in sunlight (Borovsky & Delzanno, 2019 ; Sotnikov et al., 2018 ). These techniques require dedicated, expensive engineering efforts for design, construction, and testing before they are deployed on the ground or in space.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ambient power‐line harmonics (Fedorov et al., 2021 ; Park & Helliwell, 1978 ), intentional VLF transmissions from terrestrial power lines and high‐power VLF transmitters can leak into space where they may interact with energetic electrons in the Earth's magnetosphere (Hua et al., 2020 ; Ma et al., 2017 ; Ross et al., 2019 ). Several man‐made facilities have been developed to study this wave‐particle‐interaction process including VLF transmitters (Helliwell, 1977 , 1988 ), high‐power HF facilities for modulations of natural ionosphere currents in the ionosphere (Guo et al., 2021 ), large satellite antennas driven by high power signal generators, electron beams that are modulated at VLF rates, and high‐speed neutral injections that rapidly photoionize in sunlight (Borovsky & Delzanno, 2019 ; Sotnikov et al., 2018 ). These techniques require dedicated, expensive engineering efforts for design, construction, and testing before they are deployed on the ground or in space.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of sidebands around the carrier frequency of pulses is discussed in a review by Gołkowski et al (2019) who additionally examine the frequencies of the observed echoes which are missing (see also "Discussions" later on). One can see additional results in review papers by Cohen and Gołkowski (2013), and recently by Guo et al (2021). Overall, ELF/VLF magnetospheric wave injection experiments with HAARP show that the facility injects ELF/VLF waves into the magnetosphere primarily from directly above the heated portion of the ionosphere (Golkowski et al 2011).…”
Section: Previous Results From Haarp Heatingmentioning
confidence: 97%
“…Thus, intense Pc1 pulsations can suppress the natural or artificial radiation belts. Therefore, the idea emerged to stimulate the excitation of artificial Pc1 pulsations with the use of the radio heating facilities, for example, HAARP or Sura (see review of Guo et al (2021)). However, the modulated heating of the ionosphere demands a high cost of construction and maintenance of radio-heating facilities.…”
Section: Generation Of Artificial Pc1 Pulsations By Ground Power Linesmentioning
confidence: 99%